2020
DOI: 10.1159/000507785
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Serum Phosphorus Control Associated with Overall Mortality in Patients Undergoing Peritoneal Dialysis

Abstract: Background: Serum phosphorus (SP) level is closely associated with overall mortality and cardiovascular events, while the role of SP controlled duration is not fully recognized. Here, we conducted a retrospective cohort study in our department to identify the relationship of SP controlled duration with clinical outcomes in patients undergoing peritoneal dialysis (PD). Methods: PD patients in our center from January 1, 2009, to June 30, 2019, were followed up at 2-month (the first year) or 5-month (the next fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Serum phosphate level has also been found to be a powerful independent predictor of coronary heart disease in patients with diabetes[ 28 ]. Baseline serum phosphorus level was not a risk factor for mortality after 6 mo, which is similar to findings in other studies[ 30 , 31 ]. In our study, we focused on the risk factors for mortality within the first 6 mo; therefore, we only collected the baseline serum phosphorus levels.…”
Section: Discussionsupporting
confidence: 90%
“…Serum phosphate level has also been found to be a powerful independent predictor of coronary heart disease in patients with diabetes[ 28 ]. Baseline serum phosphorus level was not a risk factor for mortality after 6 mo, which is similar to findings in other studies[ 30 , 31 ]. In our study, we focused on the risk factors for mortality within the first 6 mo; therefore, we only collected the baseline serum phosphorus levels.…”
Section: Discussionsupporting
confidence: 90%
“…Although the present study does not provide outcomes data, prior evidence has demonstrated that longer durations of sP control were independently associated with reduced mortality—a 3.2% decrease in risk for each additional month of sP control and a 38.1% decrease in risk for each additional year of sP control [ 21 ]. In that same study, a longer duration of sP control was also independently associated with lower rates of PD withdrawal.…”
Section: Discussionmentioning
confidence: 97%
“…When considering therapies to lower sP in ESKD, the need for long-term control is paramount. Gong and colleagues found a 3.2% reduced risk of mortality for each month of phosphorus control [ 28 ]. Such data highlight the need for early and prolonged reduction of sP.…”
Section: Discussionmentioning
confidence: 99%